The use of nitrogen-doped graphene supporting Pt nanoparticles as a catalyst for methanolelectrocatalytic oxidation - Xiong, B.; Zhou, Y.; Zhao, Y.; Wang, J.; Chen, X.; O’Hayre, R.; Shao, Zongping (Pergamon, 2013)
Nitrogen-doped graphene (N-G) was prepared by thermal annealing of graphene oxide in ammonia at different temperatures. The resultant N-G was used as a conductive support for Pt nanoparticles (Pt/N-G) and the electrocatalytic activity of the Pt/N-G catalysts towards methanol oxidation was examined. To investigate the microstructure and morphology of the synthesized catalysts, X-ray diffraction, scanning and transmission electron microscopy and X-ray photoelectron spectroscopy were used. The catalytic activity of the catalysts towards the oxidation of methanol was evaluated by cyclic voltammetry. Compared to a control catalyst of Pt loaded on undoped graphene, the Pt/N-G materials show higher electrochemical activity towards methanol oxidation. The excellent electrochemical performance of Pt/N-G is mainly attributed to the nitrogen doping and the uniform distribution of Pt particles on the doped graphene support. These results indicate that N-dopedgraphene has great potential as a high-performance catalyst support for fuel cell electrocatalysis.